Measurement of the tilt angle of turbulent structures in magnetically confined plasmas using Doppler reflectometry. (4th September 2019) - Pinzón, J R; Estrada, T; Happel, T; Hennequin, P; Blanco, E; Stroth, U
Abstract: The mean tilt angle of turbulent structures is a key element for describing the turbulence and its interplay with plasma flows in magnetically confined plasmas. It is a quantity predicted by theories and gyrokinetic simulations, which can provide information on the type of the dominant micro-instability, and also on the turbulence anisotropy induced by sheared flows. A new method for measuring the tilt angle of turbulent structures using Doppler reflectometry has been recently introduced (Pinzón et al 2019 Nucl. Fusion 59 074002). It is based on the time delay of the cross-correlation between microwaves backscattered at radially displaced positions. In this paper, the method is presented in detail and is successfully applied on the ASDEX Upgrade tokamak and the TJ-II stellarator. Measurements of the tilt angle in the core of both machines are reported, in the TJ-II case, for the first time.